2018
DOI: 10.1590/1678-5150-pvb-5014
|View full text |Cite
|
Sign up to set email alerts
|

Pelvimetry in Squirrel Monkeys (Saimiri scireus Linnaeus, 1758)

Abstract: Saimiri sciureus is a neotropical primate widely used in research. However, there are still difficulties regarding their reproduction in vivaria due to the high incidence of dystocia. Dystocia in primates can be caused by cephalopelvic disproportion and in Squirrel Monkeys, pregnancy of large fetuses were reported. This paper describes pelvimetry data of adult females and subadults in specimens of Squirrel Monkeys, from a research colony of Para, Brazil. Pelvic radiographs were obtained in ventrodorsal project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…in the present study was statistically higher for adult females compared to adult males and sub‐adult females. These data are in agreement with previous studies that observed a larger pelvic inlet in females than in males in adult Callithrix jacchus , 8 and a lower superior bi‐iliac diameter and smaller pelvic inlet in sub‐adult females in Saimiri scireus compared to adult females 9 . In the current study, except for the right diagonal diameter, all pelvimetry measurements in sub‐adult females were statistically similar to those of males.…”
Section: Discussionsupporting
confidence: 93%
“…in the present study was statistically higher for adult females compared to adult males and sub‐adult females. These data are in agreement with previous studies that observed a larger pelvic inlet in females than in males in adult Callithrix jacchus , 8 and a lower superior bi‐iliac diameter and smaller pelvic inlet in sub‐adult females in Saimiri scireus compared to adult females 9 . In the current study, except for the right diagonal diameter, all pelvimetry measurements in sub‐adult females were statistically similar to those of males.…”
Section: Discussionsupporting
confidence: 93%
“…These measurements were performed according to protocols established by MONTEIRO et al (2012), PINHEIRO et al (2016), andFAVORETTO et al (2018), under the following conditions: upper bi-iliac diameter (AB), drawing a straight line across the longitudinal diameter of the pelvis at the smallest diameter of the sacroiliac joint; lower bi-iliac diameter (CD), drawing a straight line parallel to the AB diameter, which was measured at the ilio-pubic junction. We also measured two diameters diagonally: the right diameter, which went from point A to D; the left diameter, which started at point B and went on to C, at the intersection point of the diagonal diameters, parallel to the upper bi-iliac and lower bi-iliac diameters, and a third transverse diameter was drawn, that is, the middle bi-iliac (EF), which went from the medial face of the right ilium to the left ilium (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Pelvimetry diameter values were obtained including the upper bi‐iliac, lower bi‐iliac, mid bi‐iliac, right diagonal, left diagonal, and sacro‐pubic. From these values, it was possible to calculate the pelvic entry area using the following formula: (mid bi‐iliac diameter/2) × (sacro‐pubic diameter/2) × π. Measurements were performed according to previous descriptions in primates 9,11,22,23,24 . The measurement points on the radiographic images in ventrodorsal projection are shown in Figure 1A.…”
Section: Methodsmentioning
confidence: 99%